Influence of particle size and morphology of Pt₃Co/C on the oxygen reduction reaction - Hlabangana, Ntandoyenkosi (Centre for Catalysis Research, 2017)
Polymer electrolyte fuel cells have shown great potential in providing clean energy with no emissions. The kinetics of the cathode reaction, i.e. the oxygen reduction reaction (ORR) are sluggish necessitating high loadings of the catalyst metal, i.e. platinum. Platinum is a limited resource and expensive. Its price has been one of the major drawbacks in wide scale commercialisation of fuel cells. In an effort to improve the activity of the catalyst and therefore reduce Pt loadings on the catalyst, Pt can be alloyed with transition metal elements (e.g. Ni, Co and Fe) to form bimetallic catalysts. Alloying has been known to improve the activity and stability of a catalyst for the ORR. The enhanced activity of the alloys originates from the modified electronic structures of the Pt in these alloy catalysts which reduces the adsorption of spectator species therefore increasing the number of active sites for the ORR (Wang et al., 2012 (2)). The aim of this study was to gain a better understanding of the influence of Pt alloy particle size and active surface morphology on the ORR activity. The Pt alloy that was investigated was Pt₃Co/C. The surface morphology was modified by varying the Pt/Pt₃Co loading on a carbon support. The catalysts were prepared using thermally induced chemical deposition. The support used was Vulcan-XC-72R. The effects of varying the metal loadings on the ORR was investigated. The loadings that were investigated were 20, 40, 60 and 80 wt. % Pt and Pt₃Co. The alloy catalysts were subjected to annealing at 900 °C and acid leaching. The catalysts were analysed using electrochemical characterisation techniques such as cyclic voltammetry, CO stripping voltammetry, rotating disk electrode and rotating ring disk electrode. Physical characterisation of the catalysts was also implemented. The techniques used were x-ray diffraction, thermogravimetric analysis and transmission electron microscopy. The Pt particles on the carbon support were found not to agglomerate significantly despite the loading being increased. This trend was also observed for the Pt₃Co/C catalysts even after heat treatment and leaching. The lack of agglomeration was credited to a new reactor system developed in this work. The particle growth increased from low loadings to high loadings for both the Pt/C and Pt₃Co/C catalysts. Particle growth was more significant for the Pt₃Co/C catalysts at high loadings. At lower loadings (20 and 40 wt. %) the particle sizes between the Pt/C and Pt₃Co/C catalysts were comparable despite the Pt₃Co/C catalysts undergoing annealing and leaching. The mass specific activity of the Pt/C catalysts was not improved by alloying with the exception of the 20 wt. % catalyst which saw an enhancement factor of 1.66. The surface specific activity of the Pt/C catalysts was improved significantly with factors of 2.40 and 3.11 being recorded for the 20 and 80 wt. % Pt₃Co/C catalysts respectively. The enhancement factors of the intermediate loadings (40 and 60 wt. %) were lower and fairly similar at 1.30 and 1.35 respectively.